Association between sex steroid hormones and α-klotho: Results from the NHANES 2013-2016 and Mendelian randomization study - Andong Guo; Pengcheng Chen; Jishuang Cao; Chenrui Wu; Sentai Ding (Experimental Gerontology)
Purpose: This study aimed to explore the association and causal links between sex steroid hormones and the anti-aging protein α-Klotho, extending to investigate the mediation effects of potential mediators. Methods: Based on data from the National Health and Nutrition Examination Survey (NHANES) 2013–2016, this study performed weighted multivariable-adjusted logistic regression to evaluate the association between sex steroid hormones and α-Klotho. Then, utilizing summary data from genome-wide association studies (GWAS), a bidirectional two-sample Mendelian randomization (MR) was conducted to assess the causal relationship between sex steroid hormones and α-Klotho. Finally, mediation analysis was conducted to delineate the influence of five identified potential mediators on the sex steroid hormones-α-Klotho association. Results: In men, significant positive correlations with α-Klotho were consistent across both unadjusted and fully adjusted models for total testosterone (TT), bio-available testosterone (Bio-T), estradiol (E2) and sex hormone-binding globulin (SHBG) (Model 3: TT: β = 3.54, 95 % CI: 1.63–5.44, P = 0.0003; Bio-T: β = 1.74, 95 % CI: 0.73–2.74, P = 0.0007; E2: β = 0.25, 95 % CI: 0.11–0.38, P = 0.0003; SHBG: β = 0.95, 95 % CI: 0.63–1.27, P < 0.0001); In premenopausal women, we detected a potential nonlinear relationship between TT levels and α-Klotho, with α-Klotho levels rising to a peak at a TT level of 72.2 ng/mL, after which they declined. Furthermore, results from MR analyses reaffirmed positive associations of TT and Bio-T with α-Klotho in men (TT: β = 3.54, 95 % CI: 1.63–5.44, P = 0.0003; Bio-T: β = 1.74, 95 % CI: 0.73–2.74, P = 0.0007). Finally, significant mediation effects were observed for uric acid (β = 0.27, 95 % CI: 0.15–0.67, P < 0.0001) and creatinine (β = 0.05, 95 % CI: 0.01–0.16, P = 0.0060), accounting for 26.7 % and 5.23 % of the total mediation effect, respectively. Conclusion: In conclusion, our results demonstrate that both TT and Bio-T enhance the expression of α-Klotho in men. The positive association observed may be partly mediated by uric acid and creatinine.